Antistatic adhesive tape for backgrinding
Patent Information
- Application Number
- JP2025059690
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
AI Technical Summary
【0010】 本発明のバックグラインド用帯電防止粘着テープは所望のレベルの帯電防止性を備え、かつ、帯電防止コート層と基材フィルムとの密着性に優れる。
Smart Images

Figure 2026166628000001_ABST
Abstract
Description
[Technical Field]
[0001] This invention relates to an antistatic adhesive tape for backgrinding. [Background technology]
[0002] In the semiconductor wafer processing process, after forming a pattern on the surface of the semiconductor wafer, a so-called backgrinding process is performed in which the back surface of the semiconductor wafer is ground to a predetermined thickness. In this backgrinding process, backgrinding tape (surface protection tape) is applied to the surface (pattern side) of the semiconductor wafer to protect the pattern.
[0003] In semiconductor wafer processing using backgrinding tape, static electricity is generated due to bonding / peeling, triboelectric charging, and spray charging. For example, static electricity is generated on semiconductor elements when bonding or peeling backgrinding tape, and during back grinding in the backgrinding process. Static electricity is also generated when the backgrinding tape is transported on a roll. This static electricity can cause problems such as damaging circuits formed on the semiconductor wafer (electrostatic discharge damage to electronic components) or making it easier for foreign matter such as dust to adhere to the circuits.
[0004] As a countermeasure against static electricity generated during the processing of semiconductor wafers as described above, a technology for imparting antistatic properties to backgrinding tape is known. For example, this can be achieved by kneading an antistatic agent into the resin that makes up the base film of the backgrinding tape, by incorporating an antistatic agent into the adhesive layer, or by providing a coating layer containing an antistatic agent (also referred to as an "antistatic coating layer") on the outermost surface of the base film or the outermost surface of the adhesive layer. For example, Patent Document 1 describes an adhesive sheet comprising a base layer and an adhesive layer provided on one side of the base layer, wherein in a peel test at a peeling speed of 300 mm / min, the peeling band voltage generated when the adhesive sheet is peeled from the release film is 500V or less. An example in Patent Document 1 describes an adhesive sheet that achieves the above-mentioned peeling band voltage from the release film, in which at least an antistatic agent is contained in the adhesive layer. Furthermore, Patent Document 2 describes an adhesive sheet for fixing electronic components having a base film and an adhesive layer, wherein an outer antistatic layer and an outer protective layer are provided in that order on the side of the base film opposite to the side on which the adhesive layer is formed. [Prior art documents] [Patent Documents]
[0005] [Patent Document 1] Japanese Patent Publication No. 2023-133232 [Patent Document 2] International Publication No. 2021 / 117398 [Overview of the project] [Problems that the invention aims to solve]
[0006] With technological advancements, semiconductor wafer processing tends to generate more static electricity. For example, the widespread adoption of flip-chip mounting methods has increased the need for higher density bumps and narrower wiring pitches on the wafer surface, making semiconductor wafers more susceptible to static electricity than ever before. Furthermore, the increased speed of backgrinding tape peeling also contributes to increased static electricity generation. Therefore, backgrinding tapes require further improvements in their antistatic properties.
[0007] The inventors attempted to impart antistatic properties to backgrinding tape by laminating an antistatic coating layer onto the outermost surface of the base film constituting the backgrinding tape. However, it was found that during the manufacturing and use of the backgrinding tape, such as during transport, the antistatic coating layer located on the outermost layer of the tape partially peels off. Peeling off the antistatic coating layer is particularly likely to occur when the antistatic coating layer comes into contact with other components, such as when it comes into contact with transport rollers or during surface cleaning treatment using adhesive tape to remove foreign matter such as dust. When the antistatic coating layer peels off, the antistatic performance fluctuates, and there is a risk that the desired antistatic properties will not be achieved in subsequent processes. Therefore, it is necessary to improve the adhesion between the antistatic coating layer and the base film.
[0008] The present invention aims to provide an antistatic adhesive tape for backgrinding that possesses desirable excellent antistatic properties and excellent adhesion between the antistatic coating layer and the base film. [Means for solving the problem]
[0009] The above-mentioned problems of the present invention were solved by the following means. <1> An antistatic adhesive tape for backgrinding having an antistatic coating layer, a base film, and an adhesive layer in this order, The antistatic coating layer contains carbon nanotubes as an antistatic agent, An antistatic adhesive tape for backgrinding that satisfies the following conditions (1) to (3), provided that before the following treatment A, the surface resistivity measured from the antistatic coating layer side in an atmosphere of 23°C and 50% relative humidity is defined as surface resistivity R1, and after the following treatment A, the surface resistivity measured from the antistatic coating layer side in an atmosphere of 23°C and 50% relative humidity is defined as surface resistivity R2. (1) The surface resistivity R1 is 1.0 × 10 4 ~1.0×10 10 It is Ω / sq., (2) The surface resistivity R2 is 1.0 × 10 4 ~1.0×1010 Ω / sq., and (3) The surface resistivity change rate X calculated by the following (Formula I) is 1 to 80. (Formula I) Surface resistivity change rate X = Surface resistivity R2 / Surface resistivity R1 (Treatment A) In an atmosphere at a temperature of 23°C and a relative humidity of 50%, pressure-sensitive adhesive tape z (manufactured by Nitto Denko Corporation, product number: No.31B, 25 mm width) is bonded to the entire surface of the antistatic coat layer of the antistatic pressure-sensitive adhesive tape for back grinding by reciprocating a 2 kg roller 3 times from above as a pressurization condition, and after leaving to stand for 1 hour, the pressure-sensitive adhesive tape z is peeled off under the conditions of a peeling angle of 180 degrees and a tensile speed of 300 mm / min. <2> The antistatic pressure-sensitive adhesive tape for back grinding according to <1>, wherein the antistatic coat layer contains at least one of a polyurethane resin and an acrylic resin containing a polyether structure. <3> The antistatic pressure-sensitive adhesive tape for back grinding according to <1> or <2>, wherein the thickness of the antistatic coat layer is 10 to 200 nm. <4> The antistatic pressure-sensitive adhesive tape for back grinding according to any one of <1> to <3>, wherein the base film contains a polyester resin. Effects of the Invention
[0010] The antistatic pressure-sensitive adhesive tape for back grinding of the present invention has a desired level of antistatic property, and is excellent in adhesion between the antistatic coat layer and the base film. Brief Description of the Drawings
[0011] [Figure 1] Figure 1 is a schematic cross-sectional view schematically showing one embodiment of the antistatic pressure-sensitive adhesive tape for back grinding of the present invention. Note that hatching indicating the cross section is omitted in Figure 1. Modes for Carrying Out the Invention
[0012] In this invention, the surface of a semiconductor wafer refers to the surface of the semiconductor wafer that has irregularities, that is, the surface on which an integrated circuit (circuit pattern) is formed. The surface opposite to this surface is referred to as the back surface. In this invention, a numerical range represented using "~" means a range that includes the numbers written before and after "~" as the lower limit and upper limit, respectively. In this invention, "(meth)acrylic" is used to mean that it includes either "acrylic" or "methacrylic" or both.
[0013] [Anti-static adhesive tape for backgrinding] The antistatic adhesive tape for backgrinding of the present invention (hereinafter also simply referred to as "the tape of the present invention") comprises an antistatic coating layer, a base film, and an adhesive layer in this order. The antistatic coating layer contains carbon nanotubes as an antistatic agent. The tape of the present invention, when the surface resistivity measured from the antistatic coating layer side in an atmosphere of 23°C and 50% relative humidity before the following treatment A is defined as surface resistivity R1, and the surface resistivity measured from the antistatic coating layer side in an atmosphere of 23°C and 50% relative humidity after the following treatment A is defined as surface resistivity R2, The following conditions (1) to (3) must be met. (1) Surface resistivity R1 is 1.0 × 10 4 ~1.0×10 10 It is Ω / sq., (2) Surface resistivity R2 is 1.0 × 10 4 ~1.0×10 10 It is Ω / sq., (3) The surface resistivity change rate X calculated by the following formula (Equation I) is between 1 and 80. (Equation I) Surface resistivity change rate X = Surface resistivity R2 / Surface resistivity R1 <Process A> In an atmosphere at a temperature of 23°C and a relative humidity of 50%, adhesive tape z (manufactured by Nitto Denko Corporation, product number: No. 31B, 25 mm width) is bonded to the entire surface of the antistatic coat layer of the aforementioned antistatic pressure-sensitive adhesive tape for back grinding by reciprocating a 2 kg roller 3 times from above as a pressure condition, and after leaving it to stand for 1 hour, the adhesive tape z is peeled off under the conditions of a peeling angle of 180 degrees and a tensile speed of 300 mm / min. More specifically, each of the surface resistivities R1 and R2 is a value measured by the method described in the Examples mentioned later. The measurement of the surface resistivity is performed before curing by radiation when the pressure-sensitive adhesive layer of the tape of the present invention is a radiation-curable type.
[0014] The tape of the present invention is less prone to partial falling-off of the antistatic coat layer even when coming into contact with other members during conveyance in the production and use of this tape, suppresses fluctuations in antistatic performance during production and use, and stably exhibits desired antistatic performance.
[0015] The surface resistivity R1 is 1.0×10 5 ~1.0×10 10 Ω / sq., preferably 1.0×10 6 ~1.0×10 10 Ω / sq., more preferably 1.0×10 7 ~1.0×10 9 Ω / sq.. The surface resistivity R2 is 1.0×10 5 ~1.0×10 10 Ω / sq., preferably 1.0×10 6 ~1.0×10 10 Ω / sq., more preferably 1.0×10 7 ~1.0×10 9 Ω / sq.. The surface resistivities R1 and R2 can be controlled by the content of carbon nanotubes contained in the antistatic coat layer, the type of binder polymer constituting the antistatic coat layer, the thickness of the antistatic coat layer, and the like.
[0016] The surface resistivity change rate X is preferably 1 to 70, more preferably 1 to 50, even more preferably 1 to 30, and still more preferably 1 to 10.
[0017] The surface resistivity R4 of the tape of the present invention, measured from the adhesive layer side before the above-mentioned treatment A, under an atmosphere of 23°C and 50% relative humidity, is not particularly limited. 6 ~1.0×10 12 Ω / sq. is preferred.
[0018] The form of the tape of the present invention will be described. Figure 1 shows one embodiment of a preferred layer configuration of the tape of the present invention. The tape 200 of the present invention comprises, in this order, an antistatic coating layer 10, a base film 20, and an adhesive layer 30. In the present invention, the laminate of the antistatic coating layer 10 and the base film 20 may be referred to as the base film 100 with an antistatic coating layer. The tape 200 of the present invention may or may not have, in addition to the antistatic coating layer 10, another antistatic coating layer 10b (not shown in Figure 1) between the base film 20 and the adhesive layer 30. Preferably, the tape of the present invention has only the antistatic coating layer 10 and not the antistatic coating layer 10b. In the tape 200 of the present invention, no other layers are laminated on the side of the antistatic coating layer 10, and the antistatic coating layer 10 is the outermost layer located on the side of the tape 200 of the present invention that is different from the adhesive layer 30. Furthermore, the tape 200 of the present invention may further include a release film (not shown in Figure 1) on the adhesive layer 30 for protecting the adhesive layer 30. The tape 200 of the present invention may be in the form of a laminated sheet having at least an antistatic coating layer 10, a base film 20, and an adhesive layer 30, or it may be in the form of this laminate wound into a roll. Here, in the present invention, "antistatic coating layer side" means the side of the antistatic coating layer 10 (opposite side from the adhesive layer 30) in the case of a layer configuration of antistatic coating layer 10 - base film 20 - adhesive layer 30. Even if the tape of the present invention has an additional antistatic coating layer 10b between the base film and the adhesive layer, the "antistatic coating layer side" is the side of the base film that has the antistatic coating layer 10 (the side opposite to the adhesive layer 30).
[0019] The components constituting the tape of the present invention will be described below.
[0020] (1) Base film 20 The resin constituting the base film 20 used in the tape 200 of the present invention (in this invention, "resin" includes elastomers and rubbers) is not particularly limited, and plastics, rubbers, etc., that are commonly used as materials constituting base films in the art to which the present invention belongs can be used. Examples of resins constituting the base film 20 include polyolefin resins consisting of homopolymers or copolymers of monomers containing ethylenically unsaturated groups, such as polyethylene (including low-density polyethylene and high-density polyethylene (HDPE)), polypropylene, ethylene-propylene copolymer, polybutene-1, poly-4-methylpentene-1, ethylene-vinyl acetate copolymer, ethylene-ethyl acrylate copolymer, ethylene-methyl acrylate copolymer, ethylene-acrylic acid copolymer, and ionomers; engineering plastics such as polyester resins (including polyethylene terephthalate and polyethylene naphthalate), polycarbonate resins, polyurethane resins, and polymethyl methacrylate resins; synthetic rubbers such as styrene-ethylene-butene copolymers or styrene-ethylene-pentene copolymers; and thermoplastic elastomers such as polyamide-polyol copolymers. The resin constituting the base film 20 may be one of the above resins, or a combination of two or more. Furthermore, the base film 20 may be a single layer or a multi-layered structure. For example, it can be a laminate of a layer made of high-density polyethylene and a layer made of ethylene-vinyl acetate copolymer. Furthermore, the base film 20 may contain additives other than the resin mentioned above, such as colorants and antioxidants, as needed, to the extent that they do not affect its physical properties. The resin constituting the base film 20 preferably includes at least one of a polyolefin resin and a polyester resin. Polyolefin resins are preferred because they have excellent expandability, and polyester resins are preferred because they exhibit excellent heat resistance and are superior in preventing wafer cracking due to backside grinding. The proportion of polyester resin in the resin constituting the base film 20 may be, for example, 80% by mass or more, preferably 90% by mass or more, more preferably 95% by mass or more, and even more preferably 97% by mass or more. The resin constituting the base film 20 may also be polyester resin. The same applies to the proportion of at least one type (or the total of two or more types) of polyolefin resin and polyester resin in the resin constituting the base film 20. In the above description concerning the proportion of polyester resin, "polyester resin" can be read as "at least one type (or the total of two or more types) of polyolefin resin and polyester resin."
[0021] The thickness of the base film 20 is preferably 30 to 120 μm, more preferably 40 to 100 μm, and even more preferably 40 to 90 μm. If the base film 20 is multi-layered, the "thickness of the base film 20" mentioned above refers to the sum of the thicknesses of all the layers that make up the base film 20.
[0022] (2) Antistatic coating layer 10 The antistatic coating layer 10 will now be described. Unless otherwise specified, all matters other than its placement on the base film 20 can also be applied to the antistatic coating layer 10b. The antistatic coating layer 10 contains carbon nanotubes as an antistatic agent. The antistatic coating layer 10 also typically contains a binder polymer.
[0023] (Antistatic agent) Carbon nanotubes (hereinafter sometimes simply referred to as "CNTs") may be either single-walled carbon nanotubes (SWCNTs) or multi-walled carbon nanotubes (MWCNTs). MWCNT is constructed by stacking multiple cylindrical carbon walls of different diameters in a multilayered arrangement around a central axis, with the carbon walls forming a hexagonal network structure or a spiral pattern in multiple layers. Preferably, the MWCNT has 2 to 30 layers of carbon walls, and more preferably 2 to 15 layers. Furthermore, the carbon nanotubes may be dispersed individually in the antistatic coating layer 10, or they may be dispersed in bundles of multiple nanotubes.
[0024] Furthermore, when forming the antistatic coating layer 10, it is preferable to prepare an antistatic coating layer composition as described later and incorporate it as a dispersion liquid in which the CNTs are dispersed in a dispersion medium. When the dispersion medium is water or a mixture of water and an alcohol-based solvent, it is preferable to use a dispersant for dispersing the CNTs. There are no particular restrictions on the dispersant, and dispersants commonly used as dispersants for CNTs can be used. Examples include nonionic surfactants and anionic surfactants, with anionic surfactants such as alkylbenzene sulfonates (octylbenzene sulfonate, nonylbenzene sulfonate, dodecylbenzene sulfonate, etc.) being preferred. In addition, dispersants for CNTs manufactured by BYK that are not classified as binder polymers as described later (those that do not have film-forming properties and do not contribute to the development of adhesion with the base film 20) can also be used. The CNT dispersant described above is typically a component that remains in the antistatic coating layer 10. Furthermore, in the descriptions concerning the proportion of carbon nanotubes in the antistatic agent contained in the antistatic coating layer 10 described later, and in the descriptions concerning the content of the antistatic agent in the antistatic coating layer 10 described later, the carbon nanotube content shall be calculated including the CNT dispersant mentioned above.
[0025] The proportion of carbon nanotubes in the antistatic agent contained in the antistatic coating layer 10 is preferably 95% by mass or more, and more preferably 98% by mass or more. It is preferable that all of the antistatic agent contained in the antistatic coating layer 10 is carbon nanotubes.
[0026] Preferably, the antistatic coating layer 10 does not contain any antistatic agents other than carbon nanotubes. Examples of antistatic agents other than carbon nanotubes include conductive polymers, conductive inorganic fine particles, metal particles or fibers, ionic compounds, ionic surfactants, etc., as described in Japanese Patent Application Publication No. 2023-133232. Examples of ionic surfactants in the above patent document include cationic surfactants, anionic surfactants, and nonionic surfactants.
[0027] (Binder polymer) The binder polymer included in the antistatic coating layer 10 is not particularly limited, as long as it can disperse the antistatic agent containing carbon nanotubes in the tape 200 of the present invention and improve the adhesion between the antistatic coating layer and the base film. Any binder polymer commonly used as an antistatic agent dispersant or binder polymer that has film-forming properties and can exhibit adhesion to the base film 20 can be used. The binder polymer preferably includes at least one of acrylic resin and polyurethane resin, and more preferably an acrylic resin. The proportion of at least one of acrylic resin and polyurethane resin in the binder polymer (or the total proportion if there are two or more) may be, for example, 80% by mass or more, preferably 90% by mass or more, more preferably 95% by mass or more, and even more preferably 97% by mass or more. The binder polymer in the antistatic coating layer may be either acrylic resin or polyurethane resin.
[0028] Acrylic resin refers to a resin in which the polymer constituting the acrylic resin is a copolymer having (meth)acrylic acid ester as a constituent component (hereinafter referred to as "(meth)acrylic acid ester copolymer"). The content of (meth)acrylic acid ester constituent in the (meth)acrylic acid ester copolymer is 50 to 100% by mass, preferably 80 to 100% by mass. Preferred examples of the above-mentioned (meth)acrylic acid ester copolymer include a (meth)acrylic acid ester copolymer comprising a constituent unit derived from at least two of the following: a (meth)acrylic acid ester monomer, a (meth)acrylic acid ester monomer having a functional group such as a hydroxyl group or a polyether structure (poly(alkylene oxy) structure) and / or a polar group, and (meth)acrylic acid. Examples of (meth)acrylic acid ester monomers include cycloalkyl (meth)acrylates and alkyl (meth)acrylates in which the alkyl group has 1 to 18 carbon atoms (preferably 1 to 12, more preferably 1 to 8, and even more preferably 1 to 4). Specifically, examples include butyl (meth)acrylate, 2-butyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, lauryl (meth)acrylate, methyl (meth)acrylate, ethyl (meth)acrylate, isopropyl (meth)acrylate, tridecyl (meth)acrylate, myristyl (meth)acrylate, cetyl (meth)acrylate, stearyl (meth)acrylate, cyclohexyl (meth)acrylate, and benzyl (meth)acrylate. Furthermore, examples of (meth)acrylic acid ester monomers having functional groups such as hydroxyl groups include (meth)acrylic acid ester monomers in which the cycloalkyl group, benzyl group, or alkyl group constituting the ester in the above-mentioned (meth)acrylic acid ester has a hydroxyl group, and hydroxyalkyl (meth)acrylates are preferred, for example, 2-hydroxyethyl (meth)acrylate. Furthermore, examples of (meth)acrylic acid ester monomers having a polyether structure include glycol-based acrylic ester monomers such as polyethylene glycol (meth)acrylate, polypropylene glycol (meth)acrylate, methoxyethylene glycol (meth)acrylate, and methoxypolypropylene glycol (meth)acrylate, with methoxyethylene glycol (meth)acrylate being preferred from the viewpoint of interaction (dispersibility) with antistatic agents. Furthermore, the (meth)acrylic acid ester copolymer may also contain, in addition to the above-mentioned constituent units, constituent units derived from carboxyl group-containing monomers such as crotonic acid, maleic acid, itaconic acid, fumaric acid, acrylamide N-glycolic acid, and cinnamic acid, as well as constituent units derived from copolymerizable monomers such as vinyl acetate, styrene, and acrylonitrile.
[0029] From the viewpoint of further improving interlayer adhesion, it is preferable that the acrylic resin includes an acrylic resin containing a polyether structure. The content of the acrylic resin containing a polyether structure in the polymer constituting the acrylic resin is preferably 80% by mass or more, and more preferably 90% by mass or more. It is also possible that all of the polymer constituting the acrylic resin is an acrylic resin containing a polyether structure. Specific examples of acrylic resins containing a polyether structure are as described above, but preferred embodiments are described in more detail below. An acrylic resin containing a polyether structure refers to a copolymer resin having (meth)acrylic acid ester as a constituent component and containing polyether bonds. The content of the (meth)acrylic acid ester component in the acrylic copolymer containing a polyether structure is 50 to 100% by mass, preferably 80 to 100% by mass. The polyether structure contained in the acrylic copolymer containing the above-mentioned polyether bond refers to a poly(alkylene oxy) structure. In the poly(alkyleneoxy) structure, the alkylene structure preferably has 1 to 6 carbon atoms, more preferably 1 to 3, and even more preferably 1 to 2 carbon atoms. Examples include methylene, ethylene, propylene, butylene, pentylene, and hexylene. The number-average number of repeats in the poly(alkylene oxy) structure is preferably 1 to 40, more preferably 2 to 30, and even more preferably 3 to 25. Examples of poly(alkyleneoxy) structures include poly(ethyleneoxy), poly(propyleneoxy), and poly(butyleneoxy) structures. In the acrylic copolymer containing the polyether structure described above, the polyether structure in the acrylic copolymer adsorbs to the antistatic agent through interaction, and the polyether-containing side chains containing the polyether structure spread stably in the dispersion medium, maintaining a dispersed state without re-aggregation due to steric repulsion between the side chains. As a result, the antistatic agent can be dispersed in the antistatic coating layer 10 with better dispersibility, and consequently, superior antistatic performance can be achieved. The acrylic copolymer containing the above-described polyether structure may have the polyether bond in either the main chain or the side chain of the polymer, as long as the effects of the present invention are achieved, and it is preferable that the bond be in the side chain. As the acrylic copolymer containing the polyether linkage described above, a comb-shaped polymer structure having a polyether linkage in the side chain portion of the acrylic copolymer is preferred. Examples of acrylic copolymers containing the above-mentioned polyether linkage include the DISPERBYK series 2000 and 2001 (both trade names, manufactured by BYK).
[0030] Polyurethane resin is a polymer having urethane bonds within its molecule, and is obtained by reacting a polyether polyol and / or polyester polyol having hydroxyl groups with a polyisocyanate compound. Examples of the above-mentioned polyether polyols include polyethylene glycol, polypropylene glycol, polyethylene propylene glycol, and polytetramethylene ether glycol. Furthermore, the above polyester polyols include polycarboxylic acids such as malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, sebacic acid, fumaric acid, maleic acid, terephthalic acid, or their acid anhydrides, and ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, dipropylene glycol, tripropylene glycol, butanediol, 1,3-butanediol, 1,4-butanediol, 2,3-butanediol, 2-methyl-1,3-propanediol, 1,5-pentanediol, neopentyl glycol, 1,6-hexanediol, 3-methyl-1,5-pentanediol, and 2-methyl-2,4-pentanediol. Examples of reaction products with polyhydric alcohols such as tandiol, 2-methyl-2-propyl-1,3-propanediol, 1,8-octanediol, 2,2,4-trimethyl-1,3-pentanediol, 2-ethyl-1,3-hexanediol, 2,5-dimethyl-2,5-hexanediol, 1,9-nonanediol, 2-methyl-1,8-octanediol, 2-butyl-2-ethyl-1,3-propanediol, 2-butyl-2-hexyl-1,3-propanediol, cyclohexanediol, bishydroxymethylcyclohexane, dimethanolbenzene, bishydroxyethoxybenzene, alkyldialkanolamines, and lactonediols. Examples of the above polyisocyanate compounds include aromatic ring-containing diisocyanates such as tolylene diisocyanate, xylylene diisocyanate, methylenediphenyl diisocyanate, and phenylene diisocyanate; aliphatic diisocyanates such as methylene diisocyanate, propylene diisocyanate, lysine diisocyanate, trimethylhexamethylene diisocyanate, and hexamethylene diisocyanate; and alicyclic diisocyanates such as cyclohexane diisocyanate, methylcyclohexane diisocyanate, and isophorone diisocyanate. Furthermore, polyurethane may have basic adsorption groups, such as tertiary amino groups, in its molecule. Furthermore, polyurethanes containing a polyether structure or a polyester structure in the side chains are preferred. Examples of such polyurethanes include BYK-9076 and the DISPERBYK series 182, 161, 162, 163, 2163, and 2164 (all are product names, manufactured by BYK).
[0031] The antistatic coating layer 10 may contain a binder polymer other than the polyurethane resin and acrylic resin (hereinafter also referred to as "other binder polymer"), within the range that achieves the effects of the present invention. As the other binder polymer, there are no particular limitations, as long as it can achieve the effects of the present invention, and any binder polymer used in an antistatic agent-containing coating layer can be used.
[0032] The proportion of at least one (or the sum of two or more) polyurethane resin and acrylic resin in the binder polymer contained in the antistatic coating layer 10 may be, for example, 80% by mass or more, preferably 90% by mass or more, more preferably 95% by mass or more, and even more preferably 97% by mass or more. It is also preferable that all of the binder polymer contained in the antistatic coating layer be at least one of polyurethane resin and acrylic resin.
[0033] The thickness of the antistatic coating layer 10 is not particularly limited as long as the surface resistivity R1, surface resistivity R2, and surface resistivity change rate X satisfy the above (1) to (3). For example, the thickness of the antistatic coating layer 10 is preferably 10 to 200 nm, more preferably 15 to 180 nm, even more preferably 20 to 160 nm, and even more preferably 20 to 140 nm. If the tape 200 of the present invention has an antistatic coating layer 10b, it is preferable that the thickness of this antistatic coating layer 10b is also within the above range.
[0034] In the antistatic coating layer 10, the carbon nanotube content in the antistatic coating layer 10 can be, for example, 10 to 80% by mass, preferably 20 to 70% by mass, and more preferably 30 to 50% by mass. In the antistatic coating layer 10, the content of the polymer binder in the antistatic coating layer 10 can be, for example, 20 to 90% by mass, preferably 30 to 80% by mass, and more preferably 50 to 70% by mass. Furthermore, the thickness of the antistatic coating layer 10 is calculated as a theoretical value of the film thickness after drying, based on the concentration of the coating liquid and the thickness during coating.
[0035] Furthermore, the antistatic coating layer 10 may contain additives such as dispersants, colorants, antioxidants, plasticizers, and curing agents, in addition to the components mentioned in the above description of the antistatic agent and binder polymer, as needed, within a range that achieves the effects of the present invention.
[0036] The antistatic coating layer 10 and the antistatic coating layer 10b may have the same or different constituent materials such as the antistatic agent and binder polymer, the content of the constituent materials, and the thickness of the layers.
[0037] (3) Adhesive layer 30 The adhesive layer 30 used in the tape 200 of the present invention may be any layer containing an adhesive, and for example, it may be formed using an adhesive composition. The adhesive layer 30 is used in contact with the uneven surface of the wafer when the tape 200 of the present invention is bonded to the wafer.
[0038] The adhesive constituting the adhesive layer 30 may be a radiation-curing adhesive that hardens upon irradiation, or it may be a radiation-non-curing adhesive that does not harden upon irradiation.
[0039] The adhesive base polymer is not particularly limited, but is preferably a (meth)acrylic polymer. A (meth)acrylic polymer means a copolymer having (meth)acrylic acid ester as a constituent unit. Examples of (meth)acrylic polymers include (meth)acrylic acid ester copolymers consisting of constituent units derived from (meth)acrylic acid ester monomers, or constituent units derived from (meth)acrylic acid monomers and constituent units derived from (meth)acrylic acid. Here, as the (meth)acrylic acid ester monomer, for example, the (meth)acrylic acid ester monomer used in the antistatic coating layer 10 described above, or a (meth)acrylic acid ester monomer having a functional group such as a hydroxyl group can be used.
[0040] The mass-average molecular weight of the adhesive-based polymer is preferably around 200,000 to 1,500,000, and more preferably 700,000 to 1,200,000, from the viewpoint of suppressing contamination of the wafer surface and suppressing gelation during synthesis and coating.
[0041] If the adhesive layer 30 is radiation-curable, in order to make the adhesive layer 30 radiation-polymerizable, the adhesive layer 30 may contain, in addition to the (meth)acrylic polymer, a compound having radiation-polymerizable ethylenically unsaturated groups (radiation-curable unsaturated carbon-carbon double bonds) (preferably a polymerizable compound with a molecular weight of 500 to 20000). It is also preferable to introduce ethylenically unsaturated groups into the (meth)acrylic polymer itself (a base polymer having ethylenically unsaturated groups is referred to as a "(meth)acrylic polymer having ethylenically unsaturated groups"). Alternatively, ethylenically unsaturated groups may be introduced into the (meth)acrylic polymer itself, and a compound having ethylenically unsaturated groups may be included in the coexistence. Furthermore, the adhesive preferably contains a crosslinking agent. Furthermore, if the adhesive is radiation-curable, it is preferable to include a photopolymerization initiator.
[0042] - (meth)acrylic polymer having ethylenically unsaturated groups The iodine value, which is an indicator of the amount of double bonds contained in the (meth)acrylic polymer having ethylenically unsaturated groups, is preferably 0.5 to 30, and more preferably 0.8 to 30, from the viewpoint of obtaining an effect of reducing adhesiveness due to radiation irradiation and preventing excessive radiation hardening. Furthermore, (meth)acrylic polymers having ethylenically unsaturated groups preferably have a glass transition temperature (Tg) of -70°C to 0°C, from the viewpoint of heat resistance to the heat generated during the wafer processing process. The acid value of the (meth)acrylic polymer having ethylenically unsaturated groups [the number of mg of potassium hydroxide required to neutralize the free fatty acids present in 1 g of polymer] is preferably 0.5 to 30 mg KOH / g, and more preferably 1 to 20 mg KOH / g. The hydroxyl value of (meth)acrylic polymers having ethylenically unsaturated groups [the number of mg of potassium hydroxide required to neutralize the acetic acid bonded to the hydroxyl group when 1 g of polymer is acetylated] is preferably 5 to 100 mg KOH / g, and more preferably 10 to 80 mg KOH / g.
[0043] The (meth)acrylic polymer having an ethylenically unsaturated group may be produced by any means, but a preferred method is to introduce an ethylenically unsaturated group into the side chain of the (meth)acrylic polymer by reacting a compound having an ethylenically unsaturated group and a functional group (β) that reacts with the functional group (α) in the polymer with a (meth)acrylic polymer having a functional group (α) in its side chain. The functional group (α) and the functional group (β) may each be one type or two or more types.
[0044] There are no particular limitations on the ethylenically unsaturated group, but (meth)acryloyl group, (meth)acryloyloxy group, (meth)acryloylamino group, allyl group, 1-propenyl group, and vinyl group are preferred, with (meth)acryloyl group or (meth)acryloyloxy group being more preferred. Examples of functional group (β) that react with functional group (α) include carboxyl group, hydroxyl group, amino group, sulfanyl group, cyclic acid anhydride group, epoxy group, and isocyanate group.
[0045] Here, if one of the functional groups (α) and (β) is a carboxyl group, hydroxyl group, amino group, sulfanyl group, or cyclic acid anhydride group, the other functional group may be an epoxy group or an isocyanate group. If one of the functional groups is a cyclic acid anhydride group, the other functional group may be a carboxyl group, hydroxyl group, amino group, or sulfanyl group. If one of the functional groups is an epoxy group, the other functional group may also be an epoxy group.
[0046] (Meth)acrylic polymers having a functional group (α) in the side chain are obtained by polymerizing at least one of (meth)acrylic acid esters, (meth)acrylic acid, and (meth)acrylamide having a functional group (α). Examples of functional group (α) include carboxyl groups, hydroxyl groups, amino groups, sulfanyl groups, cyclic acid anhydride groups, epoxy groups, and isocyanate groups, and it is preferable that at least one of a carboxyl group and a hydroxyl group be included, and more preferably that at least one of a hydroxyl group be included.
[0047] Examples of monomers having a functional group (α) include (meth)acrylic acid, methacrylic acid, cinnamic acid, itaconic acid, fumaric acid, phthalic acid, 2-hydroxyalkyl (meth)acrylate, glycol mono(meth)acrylate, N-methylol(meth)acrylamide, allyl alcohol, N-alkylaminoethyl (meth)acrylate, (meth)acrylamide, maleic anhydride, itaconic anhydride, fumaric anhydride, phthalic anhydride, glycidyl (meth)acrylate, and allyl glycidyl ether, and polyisocyanate compounds in which a portion of the isocyanate group is urethaned with monomers having a hydroxyl group or carboxyl group and a radiation-curable carbon-carbon double bond. Among these, (meth)acrylic acid, 2-hydroxyalkyl (meth)acrylate, or glycidyl (meth)acrylate is preferred, (meth)acrylic acid or 2-hydroxyalkyl (meth)acrylate is more preferred, and 2-hydroxyalkyl (meth)acrylate is even more preferred. The monomer having the functional group (α) may be one type or two or more types.
[0048] The (meth)acrylic polymer having an ethylenically unsaturated group is preferably a copolymer with a monomer other than the monomer having the above-mentioned functional group (α) (for example, other monomers such as (meth)acrylic acid esters that do not have the above-mentioned functional group (α)). Examples of (meth)acrylic acid esters that do not have the above-mentioned functional group (α) include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, decyl (meth)acrylate, and dodecyl (meth)acrylate methacrylate. The (meth)acrylic acid ester that does not have the above-mentioned functional group (α) may be used individually or in combination of two or more types.
[0049] The polymerization reaction of (meth)acrylic polymers having ethylenically unsaturated groups may be carried out by solution polymerization, emulsion polymerization, bulk polymerization, or suspension polymerization. When a (meth)acrylic polymer having a functional group (α) in its side chain is synthesized by reacting it with a compound having an ethylenically unsaturated group and a functional group (β) that reacts with the functional group (α) in the polymer, a polymer with a desired acid value and hydroxyl value can be prepared by leaving unreacted functional groups.
[0050] There are no particular restrictions on the polymerization initiator used in the polymerization of (meth)acrylic polymers having ethylenically unsaturated groups. For example, radical generators such as azobis-based agents like α,α'-azobisisobutylnitrile and organic peroxide-based agents like benzoyl peroxide are commonly used. In this case, catalysts and polymerization inhibitors can be used in combination as needed, and polymers with desired molecular weights can be obtained by adjusting the polymerization temperature and polymerization time. Furthermore, it is preferable to use mercaptan or carbon tetrachloride-based solvents to adjust the molecular weight.
[0051] This section describes compounds having an ethylenically unsaturated group and a functional group (β). The ethylenically unsaturated group and functional group (β) are as described above. The isocyanate group is particularly preferred as the functional group (β).
[0052] Examples of compounds having an ethylenically unsaturated group and a functional group (β) include (meth)acrylic acid esters having an isocyanate group in the alcohol portion. For (meth)acrylic acid esters having an isocyanate group in the alcohol portion, those having an isocyanate group at the end of the alcohol portion are preferred, the number of carbon atoms other than the isocyanate group in the alcohol portion is preferably 2 to 8, and the alcohol portion is preferably a linear alkyl group. For example, 2-isocyanatoethyl (meth)acrylate is a preferred example of a (meth)acrylate having an isocyanate group in the alcohol portion.
[0053] As an adhesive in which an ethylenically unsaturated group is introduced into the adhesive base polymer itself and a compound having an ethylenically unsaturated group is present, for example, the description relating to an adhesive containing a radiation-polymerizable low molecular weight compound described in
[0059] to
[0064] of International Publication No. 2018 / 181240 can be applied.
[0054] -Crosslinking agent- The adhesive layer 30 described above preferably has a (meth)acrylic polymer having a certain degree of cross-linking structure (before the photocuring reaction if the adhesive is radiation-curable). Preferred cross-linking agents for forming the cross-linking structure include polyisocyanate compounds, melamine-formaldehyde resins, and epoxy resins, with polyisocyanate compounds being particularly preferred. The cross-linking agent may be used alone or in combination of two or more types. By incorporating a cross-linking agent, the cohesive force of the adhesive can be improved after application.
[0055] There are no particular restrictions on the polyisocyanate compounds, and examples include aromatic isocyanates such as 4,4'-diphenylmethane diisocyanate, tolylene diisocyanate, xylylene diisocyanate, 4,4'-diphenyl ether diisocyanate, and 4,4'-[2,2-bis(4-phenoxyphenyl)propane] diisocyanate, as well as hexamethylene diisocyanate, 2,2,4-trimethyl-hexamethylene diisocyanate, isophorone diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, 2,4'-dicyclohexylmethane diisocyanate, lysine diisocyanate, and lysine triisocyanate. Also, examples include adduct compounds of these isocyanate compounds with polyol compounds such as trimethylolpropane; and biuret and isocyanurate compounds of these isocyanate compounds.
[0056] Specifically, melamine-formaldehyde resins such as Nikalac MX-45 (product name, manufactured by Sanwa Chemical Co., Ltd.) and Melan (product name, manufactured by Hitachi Chemical Co., Ltd.) can be used. As the epoxy resin, TETRAD-X (trade name, manufactured by Mitsubishi Chemical Corporation) can be used.
[0057] The amount of crosslinking agent added is preferably 0.1 to 20 parts by mass, and more preferably 1.0 to 10 parts by mass, per 100 parts by mass of the adhesive base polymer, from the viewpoint of exhibiting an effect of improving cohesive force, suppressing the formation of crosslinked structures due to the rapid progress of the curing reaction, and not impairing workability. The amount can be appropriately adjusted according to the number of functional groups of the (meth)acrylic polymer having ethylenically unsaturated groups, and in order to obtain the desired adhesive properties and elastic modulus.
[0058] -Photopolymerization initiator- The photopolymerization initiator is not particularly limited as long as it reacts to radiation transmitted through the antistatic coated substrate film 100, and commonly used ones can be used. Examples include benzophenones such as benzophenone, 4,4'-dimethylaminobenzophenone, 4,4'-diethylaminobenzophenone, and 4,4'-dichlorobenzophenone; acetophenones such as acetophenone and diethoxyacetophenone; α-hydroxyketones such as oligo[2-hydroxy-2-methyl-1[4-(1-methylvinyl)phenyl]propanone] and 2-hydroxy-2-methyl-1-phenyl-1-propanone; anthraquinones such as 2-ethylanthraquinone and t-butylanthraquinone; 2-chlorothioxanthone, benzoin ethyl ether, benzoin isopropyl ether, benzyl, 2,4,5-trially-ruimidazole dimer (rophine dimer), acridine compounds, acylphosphine oxides, etc. These may be used individually, or in combination of two or more types. The amount of photopolymerization initiator added is preferably 0.1 to 10 parts by mass, and more preferably 0.5 to 7 parts by mass, per 100 parts by mass of (meth)acrylic polymer having ethylenically unsaturated groups.
[0059] -Other additives- The adhesive layer 30 may contain tackifiers, tackiness modifiers, surfactants, or other modifiers as needed. In addition, inorganic compound fillers may be added as appropriate. In the present invention, the addition of modifiers is also preferable from the viewpoint of release properties. Furthermore, the description relating to radiation-curable additives described in paragraph
[0050] of Japanese Patent Publication No. 2022-109374 can be preferably applied.
[0060] The thickness of the adhesive layer 30 is preferably 20 to 80 μm, more preferably 25 to 75 μm, and even more preferably 30 to 70 μm.
[0061] In the tape 200 of the present invention, both the adhesive layer 30 and the base film 20 preferably do not contain an antistatic agent, and preferably contain 1% by mass or less. Examples of such antistatic agents include materials commonly used for antistatic purposes. For example, conductive polymers, conductive inorganic fine particles, metal particles or fibers, ionic compounds, ionic surfactants, etc., as described in Japanese Patent Application Publication No. 2023-133232. Even in such an embodiment (where the adhesive layer 30 and / or base film 20 do not contain an antistatic agent), the tape 200 of the present invention can exhibit desired antistatic properties and water resistance.
[0062] (4) Preferred characteristics of the tape of the present invention The tape 200 of the present invention preferably has the following optical properties. The tape 200 of the present invention preferably has a transmittance of 60% or more, more preferably 70% or more, and even more preferably 80% or more, of light with a wavelength of 660 nm. When the above transmittance is satisfied, alignment can be performed during backgrinding, stealth dicing (more specifically, during SDBG (Stealth Dicing Before Grinding) processing, etc.) while optically recognizing alignment marks applied to the surface of the adherend, etc., via the tape 200 of the present invention. The above measurement of parallel light transmittance can be performed by the method described in the examples.
[0063] The tape 200 of the present invention preferably has a haze value of 30% or less, more preferably 28% or less, more preferably 25% or less, and more preferably 23% or less at a wavelength of 660 nm. When the above haze value is satisfied, alignment can be performed during backgrinding, stealth dicing (more specifically, during SDBG processing, etc.) while optically recognizing alignment marks applied to the surface of the workpiece, etc., via the tape 200 of the present invention. The above haze value can be measured by the method described in the examples.
[0064] The tape 200 of the present invention can also be provided in an embodiment that offers even greater water resistance. In this embodiment, the tape 200 of the present invention satisfies the following conditions (1b) to (3b) when the surface resistivity measured from the antistatic coating layer 10 side in an atmosphere of 23°C and 50% relative humidity after the water resistance test (B) described below is defined as the surface resistivity R3. (1b) Surface resistivity R1 is 1.0 × 10 4 ~1.0×10 10 It is Ω / sq., (2b) Surface resistivity R3 is 1.0 × 10 4 ~1.0×10 10 It is Ω / sq., (3b) The surface resistivity change rate X calculated by the following formula (Equation I) is between 1 and 80. (Equation II) Change in surface resistivity after water resistance test Y = Surface resistivity R3 / Surface resistivity R1 <Water resistance test (B)> A sample of antistatic adhesive tape for backgrinding, whose surface resistivity R1 was measured, was immersed in pure water for 10 minutes in a 120 mm x 120 mm plastic container filled with pure water at a temperature of 23°C. After that, the sample was removed, water droplets were blown off the tape surface with a blower, and then it was allowed to dry for 24 hours in an atmosphere of 23°C and 50% relative humidity. Subsequently, the surface resistivity R3 was measured in the same manner as for surface resistivity R1, in an atmosphere of 23°C and 50% relative humidity. The surface resistivity R3 is a value measured more specifically by the method described in the examples below. If the adhesive layer of the tape of the present invention is radiation-curable, the surface resistivity measurement is performed before radiation curing.
[0065] The tape of the present invention is effective in preventing the generation of static electricity that occurs when the tape is peeled off after the backgrinding process. The present invention suppresses fluctuations in antistatic performance, and stably exhibits the desired antistatic performance.
[0066] The surface resistivity R3 is 1.0 × 10⁻⁶ 5 ~1.0×10 10 Ω / sq. is preferred, and 1.0 × 10 6 ~1.0×10 9 Ω / sq. is more preferred, 1.0 × 10 7 ~1.0×10 9 Ω / sq. is even more preferable. The surface resistivity R1 and R3 can be controlled by the amount of carbon nanotubes contained in the antistatic coating layer, the type of binder polymer constituting the antistatic coating layer, the thickness of the antistatic coating layer, and so on.
[0067] The change in surface resistivity Y after the water resistance test is preferably 1 to 70, more preferably 1 to 50, even more preferably 1 to 30, and still more preferably 1 to 10.
[0068] (5) Method for manufacturing the tape of the present invention The method for manufacturing the tape 200 of the present invention is not particularly limited and can be manufactured by conventional methods. The tape 200 of the present invention can be manufactured, for example, by forming an antistatic coating layer 10 on one side of a base film 20 to form an antistatic coated base film 100, and further forming an adhesive layer 30 on the side of the antistatic coated base film 100 opposite to the antistatic coating layer 10 (the base film 20 side).
[0069] The method for manufacturing the antistatic coating layer substrate film 100 is not particularly limited. Examples include a method of directly applying a composition for forming the antistatic coating layer 10 (antistatic coating layer composition) onto the substrate film 20 using a coater such as a gravure coater, bar coater, knife coater, or roll coater, and a method of printing the antistatic coating layer composition as ink onto the substrate film 20 by relief printing, recessed printing, planar printing, flexographic printing, offset printing, or screen printing. Among these, the method of directly applying the antistatic coating layer composition onto the substrate film 20 using a gravure coater (gravure coating) is preferred from the viewpoint of being able to form a thin film antistatic coating layer 10. The dispersion medium in the film obtained by the above-mentioned coating and printing methods is removed by drying or the like to form the antistatic coating layer 10. If the tape 200 of the present invention has an antistatic coating layer 10b, the antistatic coating layer 10 and the antistatic coating layer 10b may be formed simultaneously on the base film 20, or one antistatic coating layer may be formed first, and then the remaining antistatic coating layer may be formed. The composition for the antistatic coating layer is typically a dispersion in which carbon nanotubes and a binder polymer are dispersed. The dispersion medium is not particularly limited and, depending on the type of antistatic agent and binder polymer, examples include water, alcohol-based solvents such as ethanol, organic polar solvents such as lactam-based solvents such as N-methylpyrrolidone, organic nonpolar solvents, and combinations of these solvents. Water or a mixture of water and an alcohol-based solvent is preferred in terms of handling and working environment. Furthermore, the composition for the antistatic coating layer may further contain the additives listed in the above-described antistatic coating layer 10.
[0070] The adhesive layer 30 can be formed by applying and drying a composition for forming the adhesive layer 30 (adhesive composition) onto the base film 20. Alternatively, the adhesive composition can be applied and dried onto a release film, and the resulting adhesive layer 30 can be laminated as a layer constituting the tape 200 of the present invention by laminating or transferring it onto the base film 20 or a base film 100 with an antistatic coating layer. As the solvent in the adhesive composition, solvents such as ethyl acetate can be used. [Examples]
[0071] The present invention will be described in more detail based on examples, but the present invention is not limited thereto.
[0072] <Preparation of antistatic adhesive tape for backgrinding> (Example 1) (1) Preparation of a substrate film with an antistatic coating layer An aqueous dispersion CP1 (composition for an antistatic coating layer) was prepared, which was a mixture of a carbon nanotube aqueous dispersion (product name: Conductive Coat CNT Y-545, manufactured by Chukyo Oils Co., Ltd.) as an antistatic agent and an aqueous dispersion of acrylic resin containing a polyether structure (manufactured by Chukyo Oils Co., Ltd.) (hereinafter referred to as acrylic resin a1) as a binder polymer. In this aqueous dispersion CP1, the carbon nanotube content was 30% by mass and the binder polymer content was 70% by mass. A 50 μm thick polyethylene terephthalate film (product name: Lumirror, manufactured by Toray Industries, Inc.) was used as the base film PET1. An antistatic coated base film S1 was prepared by hand-applying an aqueous dispersion CP1 to one side of this base film PET1 using an applicator so that the calculated thickness after drying was 100 nm. (2) Preparation of antistatic adhesive tape for backgrinding As an acrylic copolymer having functional groups, a copolymer consisting of 2-ethylhexyl acrylate, 2-hydroxyethyl acrylate, and methacrylic acid was prepared with a mass-average molecular weight of 750,000. Next, 2-isocyanatoethyl methacrylate was added to achieve an iodine value of 25 to prepare acrylic copolymer A with a glass transition temperature of -50°C, a hydroxyl value of 10 mg KOH / g, and an acid value of 5 mg KOH / g. To 100 parts by mass of acrylic copolymer A, 1 part by mass of a trimethylolpropane adduct-type modified form of tolylene diisocyanate (TDI-TMP adduct) as a crosslinking agent and 5 parts by mass of Esacure KIP100F (trade name, manufactured by Lamberti, a mixture of oligo[2-hydroxy-2-methyl-1[4-(1-methylvinyl)phenyl]propanone] (70%) and 2-hydroxy-2-methyl-1-phenyl-1-propanone (30%)) were added. This mixture was dissolved in ethyl acetate and stirred to prepare adhesive composition A-1. Adhesive composition A-1 was applied to a silicone-release-treated polyethylene terephthalate film (25 μm thick) using a comma coater at a linear speed of 2 m / min, and the adhesive layer was formed by passing it through a hot air drying oven set to 110°C. The obtained adhesive layer and a base film S1 with an antistatic coating layer were laminated together to produce an antistatic adhesive tape for backgrinding. During the above lamination process, the adhesive layer was laminated to the side of the base film opposite to the antistatic coating layer.
[0073] (Example 2) A 50 μm thick polyolefin film (base film PO1) with a thickness ratio of HDPE:EVA = 8:2 was fabricated by extruding high-density polyethylene (HDPE, trade name: Nipolon Hard 4010A, manufactured by Tosoh Corporation) and ethylene-vinyl acetate copolymer (EVA) resin with a vinyl acetate content of 6% (trade name: Ultrasen 510, manufactured by Tosoh Corporation). The antistatic coated substrate film S2 was prepared in the same manner as in Example 1 (1) preparation of the antistatic coated substrate film, except that the above substrate film PO1 was used instead of polyethylene terephthalate film in Example 1 (1). The antistatic adhesive tape for backgrinding in Example 2 was prepared in the same manner as in Example 1(2) preparation of the antistatic adhesive tape for backgrinding, except that the antistatic coated base film S2 was used instead of the antistatic coated base film S1 in Example 1(2).
[0074] (Example 3) The antistatic coated substrate film S3 was prepared in the same manner as in Example 1(1) preparation of the antistatic coated substrate film, except that a polyurethane resin (manufactured by Chukyo Oil & Fat Co., Ltd.) (hereinafter referred to as polyurethane resin a2) was used instead of the acrylic resin a1 containing a polyether structure in Example 1(1). The antistatic adhesive tape for backgrinding in Example 3 was prepared in the same manner as in Example 1(2) preparation of the antistatic adhesive tape for backgrinding, except that the antistatic coated base film S3 was used instead of the antistatic coated base film S1 in Example 1(2).
[0075] (Comparative Example 1) Except for the use of an isopropanol-diluted solution (diluted 50 times by weight) of a surface-coated antistatic agent AC (product name: Electro Stripper AC, manufactured by Kao Corporation, a mixture of linear alkylbenzene sulfonate sodium salt and methanol) in the preparation of the antistatic coated substrate film cS1 in the same manner as in the preparation of the antistatic coated substrate film Comparative Example 1's antistatic adhesive tape for backgrinding was prepared in the same manner as in Example 1's (2) preparation of the antistatic adhesive tape for backgrinding, except that the antistatic coated base film cS1 was used instead of the antistatic coated base film S1.
[0076] (Comparative Example 2) The antistatic coated substrate film cS2 was prepared in the same manner as in Example 1(1) preparation of the antistatic coated substrate film, except that, in Example 1(1) preparation of the antistatic coated substrate film, an isopropanol diluted solution (diluted 50 times by weight) of the surface-coated antistatic agent QN (product name: Electro Stripper QN, manufactured by Kao Corporation, a mixture of alkyltrimethylammonium chloride, isopropyl alcohol, and polyoxyethylene alkyl ether) was used instead of the aqueous dispersion CP1. Comparative Example 1's antistatic adhesive tape for backgrinding was prepared in the same manner as in Example 1's (2) preparation of the antistatic adhesive tape for backgrinding, except that the antistatic coated base film cS2 was used instead of the antistatic coated base film S1.
[0077] (Comparative Example 3) Comparative Example 3 was prepared in the same manner as in Example 1(2) preparation of the antistatic adhesive tape for backgrinding, except that the aforementioned base film PET1 was used instead of the base film S1 with the antistatic coating layer in Example 1(2).
[0078] The BG tapes 200 of Examples 1-3 and Comparative Examples 1-2 obtained in this manner have a structure in which an antistatic coating layer 10, a base film 20, and an adhesive layer 30 are laminated in this order, as shown in Figure 1. The BG tape of Comparative Example 3 has a structure in which the base film 20 and the adhesive layer 30 are laminated in this order, and is a tape that does not have an antistatic coating layer 10 on the base film 20.
[0079] Table 1 shows the antistatic agent and binder polymer contained in the antistatic coating layer 10, the resin type and thickness of the base film 20, and the type and thickness of the adhesive layer 30 for the obtained antistatic adhesive tape for backgrinding (also simply referred to as "BG tape"). Furthermore, the surface resistivity of the obtained BG tape was measured. Furthermore, the adhesive strength and optical properties of the obtained BG tape were evaluated. These results are summarized in Table 1.
[0080] <thickness> The thickness was measured on a surface plate using a spindle-type dial gauge (manufactured by Mitutoyo Corporation).
[0081] <Evaluation of antistatic performance> (Surface resistivity) The BG tape was subjected to a process of laminating and peeling off the following adhesive tape. The surface resistivity R1 and R2, as well as the rate of change in surface resistivity X, were used as indicators to evaluate the change in antistatic performance and the adhesion between the antistatic coating layer and the base film. When the antistatic coating layer is removed, the surface resistivity increases. The details of the measurement method are described below. The above BG tape was cut into a measurement-specific shape (100mm x 100mm) using the resistance chamber R12702A (manufactured by Advantest) to create a measurement sample. Using a digital ultra-high resistance / micro-current meter 8340A and a resistance chamber R12702A (both manufactured by Advantest), a voltage of 10V was applied to the antistatic coating layer side (opposite the adhesive layer) for 60 seconds under conditions of 23°C and 50% relative humidity. The surface resistivity R1 was measured by reading the current value immediately after the end of the 60-second application period. The above measurement sample was processed under the following conditions (Process A). The surface resistivity R2 was measured on the sample after Process A in the same manner as the surface resistivity R1 described above. Furthermore, the rate of change in surface resistivity X was calculated based on the following (Equation I). The surface resistivity was measured on the antistatic coating layer side, as described above. (Equation I) Surface resistivity change rate X = Surface resistivity R2 / Surface resistivity R1 (Process A) Under conditions of 23°C and 50% relative humidity, adhesive tape z (manufactured by Nitto Denko, part number: No.31B, 25mm width) was applied to the entire surface of the antistatic coating layer of the above-mentioned measurement sample (BG tape) by applying pressure with a 2kg roller three times. After standing for 1 hour, the adhesive tape z was peeled off under conditions of a peeling angle of 180 degrees and a tensile speed of 300mm / min. The above bonding was performed using a manual pressure roller (product name: APR-97, manufactured by Imada Corporation). The above peeling was performed using a peeling test machine (product name: Strograph, manufactured by Toyo Seiki Seisakusho Co., Ltd.). The above tests were conducted in accordance with JIS Z0237:2022, except for the points mentioned above. Table 1 shows the surface resistivity R1 and R2, and the rate of change of surface resistivity X. Surface resistivity R1 and surface resistivity R2 are 1.0 × 10⁻⁶ 10 If the value exceeded Ω / sq., it was marked "over".
[0082] <Adhesive strength> The adhesion between the antistatic coating layer of the BG tape and the base film was evaluated as follows, using the decrease in the adhesive strength of the adhesive tape z as an indicator. A lower adhesive strength of the adhesive tape z after the second peeling means that a larger amount of the antistatic coating layer adhered to (detached from) the adhesive tape z during the first peeling. In other words, the lower the adhesion retention rate, the lower the adhesion between the antistatic coating layer and the base film. The details of the measurement method are described below. Under conditions of 23°C and 50% relative humidity, adhesive tape z (manufactured by Nitto Denko, part number No. 31B, 25mm width) was bonded to the antistatic coating layer of BG tape by applying pressure with a 2kg roller three times. After standing for 1 hour, a sample for measurement was prepared. The adhesive strength of the obtained sample was measured by peeling the adhesive tape z using a peel tester (Strograph) at a peel angle of 180 degrees and a tensile speed of 300 mm / min. This was defined as the adhesive strength P1. Furthermore, under conditions of 23°C and 50% relative humidity, the adhesive tape z that had been peeled off during the measurement of the adhesive strength P1 was bonded to the antistatic coating layer of another BG tape, with pressure applied by rolling a 2kg roller back and forth three times. After standing for 1 hour, a peel test was performed using a peel test machine (product name: Strograph, manufactured by Toyo Seiki Seisakusho Co., Ltd.) at a tensile speed of 300mm / min and a peel angle of 180 degrees, and the adhesive strength at this time was defined as the adhesive strength P2. The adhesion retention rate was calculated from the adhesion strengths P1 and P2 using the following formula (Equation II). (Formula II) Adhesive force maintenance rate = Adhesive force P2 / Adhesive force P1 × 100 Table 1 shows the adhesive strengths P1 and P2, as well as the adhesive strength retention rate.
[0083] <Optical properties> (Total light transmittance) Total light transmittance was measured using a spectroscopic haze meter, model HSP-150VIR (product name), manufactured by Murakami Color Technology Laboratory Co., Ltd. For total light transmittance measurement, the transmittance of light at a wavelength of 660 nm was measured and defined as the total light transmittance. All measurements were performed with light incident from the substrate film side. Furthermore, the measurements were performed on each adhesive tape before energy ray curing. The results are shown in Table 1. (Haze value) The haze value was measured at a wavelength of 660 nm using a spectroscopic haze meter, model HSP-150VIR (product name), manufactured by Murakami Color Technology Laboratory Co., Ltd. All measurements were performed with light incident from the substrate film side. Furthermore, the measurements were taken before each adhesive tape was cured by energy rays. The results are shown in Table 1.
[0084] <Water resistance: Water resistance test (B)> The water resistance performance of BG tape was evaluated as follows, using the change in surface resistivity before and after immersion in pure water as an indicator. After measuring the surface resistivity R1 as described above, the BG tape sample was immersed in pure water for 10 minutes in a 120 mm x 120 mm plastic container filled with pure water at a temperature of 23°C. The sample was then removed, water droplets were blown off the tape surface with a blower, and the tape was allowed to dry for 24 hours at a temperature of 23°C and a relative humidity of 50%. Subsequently, the surface resistivity R3 was measured in the same manner as for surface resistivity R1, at a temperature of 23°C and a relative humidity of 50%. The rate of change in surface resistivity Y after the water resistance test was calculated based on the following equation (Equation II). (Equation II) Change in surface resistivity after water resistance test Y = Surface resistivity R3 / Surface resistivity R1 Table 1 shows the surface resistivity R1 and R3, and the rate of change of surface resistivity Y. Surface resistivity R1 and R3 are 1.0 × 10⁻⁶. 10 If the value exceeded Ω / sq., it was marked "over".
[0085] [Table 1]
[0086] PET1: The above polyethylene terephthalate film PO1: The above polyolefin film AC: Surface-coated antistatic agent mentioned above QN: Surface-coated antistatic agent mentioned above
[0087] The BG tape of Comparative Example 3 is a BG tape that does not have an antistatic coating layer. This BG tape has a surface resistivity R1 and a surface resistivity R2 of both 1.0 × 10⁻⁶. 10 It exceeded Ω / sq. Also, the surface resistivity R3 was 1.0 × 10⁻⁶. 10 It exceeded Ω / sq. The BG tapes of Comparative Example 1 and Comparative Example 2 had surface resistivity change rates X of 95 and 435, respectively. It is thought that the antistatic coating layer was removed due to bonding and peeling with the adhesive tape z. This can also be confirmed by the fact that the adhesion retention rate in the adhesion strength evaluation was significantly lower compared to the BG tape of Comparative Example 3, which did not have an antistatic coating layer. Furthermore, the surface resistivity change rates Y of these BG tapes were 692 and 12174, respectively, resulting in poor water resistance. The BG tapes of Examples 1 to 3 all have an antistatic coating layer, a base film, and an adhesive layer, and both surface resistivity R1 and surface resistivity R2 are 1.0 × 10⁻⁶. 4 ~1.0×10 10 The resistance is within the range of Ω / sq., and the surface resistivity change rate X is in the range of 1 to 80. These BG tapes exhibit excellent adhesion between the base film and the antistatic coating layer, as the antistatic coating layer does not detach even after bonding and peeling with adhesive tape z. This is confirmed by the smaller decrease in adhesive strength retention compared to the BG tape of Comparative Example 3. Furthermore, these BG tapes also exhibit excellent water resistance, with a surface resistivity change rate Y of 1 for each tape. Furthermore, despite containing carbon nanotubes as an antistatic agent, the BG tapes of Examples 1 to 3 exhibited optical properties equivalent to those of the BG tapes of Comparative Examples 1 and 2, which contained surfactants as an antistatic agent. [Explanation of Symbols]
[0088] 10. Antistatic coating layer 20 Base film 30 Adhesive layer 100 Antistatic coated substrate film 200 Antistatic Adhesive Tape for Backgrinding
Claims
1. An antistatic adhesive tape for backgrinding having an antistatic coating layer, a base film, and an adhesive layer in this order, The antistatic coating layer contains carbon nanotubes as an antistatic agent, An antistatic adhesive tape for backgrinding that satisfies the following conditions (1) to (3), provided that before the following treatment A, the surface resistivity measured from the antistatic coating layer side in an atmosphere of 23°C and 50% relative humidity is defined as surface resistivity R1, and after the following treatment A, the surface resistivity measured from the antistatic coating layer side in an atmosphere of 23°C and 50% relative humidity is defined as surface resistivity R2. (1) The surface resistivity R1 is 1.0 × 10 4 ~1.0 x 10 10 Ω / sq. (2) The surface resistivity R2 is 1.0 × 10 4 ~1.0 x 10 10 Ω / sq. (3) The surface resistivity change rate X calculated by the following formula (Equation I) is between 1 and 80. (Equation I) Surface resistivity change rate X = Surface resistivity R² / Surface resistivity R¹ (Process A) Under conditions of a temperature of 23°C and a relative humidity of 50%, adhesive tape z (manufactured by Nitto Denko, part number: No. 31B, 25 mm wide) is applied to the entire surface of the antistatic coating layer of the antistatic adhesive tape for backgrinding by applying pressure with a 2 kg roller three times. After standing for one hour, the adhesive tape z is peeled off under conditions of a peeling angle of 180 degrees and a tensile speed of 300 mm / min.
2. The antistatic adhesive tape for backgrinding according to claim 1, wherein the antistatic coating layer comprises at least one of a polyurethane resin and an acrylic resin containing a polyether structure.
3. The antistatic adhesive tape for backgrinding according to claim 1, wherein the thickness of the antistatic coating layer is 10 to 200 nm.
4. The antistatic adhesive tape for backgrinding according to claim 1, wherein the base film contains polyester resin.
Citation Information
Patent Citations
Pressure sensitive adhesive sheet
JP2023133232A
Adhesive sheet for fixing electronic member
WO2021117398A1